Is there lower utilisation of hospice care services during end-of-life care for people living with HIV? A population-based cohort study. Issue 3 (14th March 2022) - Chan, Shang-Yih; Lai, Yun-Ju; Ko, Ming-Chung; Chen, Yu-Yen; Tsai, Yi-Fan; Hsu, Li-Fei; Ku, Po-Wen; Chen, Li-Jung; Chuang, Pei-Hung; Chen, Chu-Chieh; Yen, Yung-Feng
Abstract : Objective: Hospice care could improve the quality of life among advanced HIV patients during end-of-life (EOL) treatment. However, providing hospice care services for people living with HIV (PLWH) is challenging due to HIV-related stigma. This nationwide cohort study aims to determine the utilisation of hospice care services among PLWH and HIV-negative individuals during EOL treatment. Design: A retrospective cohort study. Setting: From 2000 to 2018, we identified adult PLWH from the Taiwan centres for disease control HIV Surveillance System. Individuals who had positive HIV-1 western blots were regarded as HIV-infected. Age-matched and sex-matched controls without HIV infection were selected from the Taiwan National Health Insurance Research Database for comparison. All PLWH and controls were followed until death or 31 December 2018. Participants: 32 647 PLWH and 326 470 HIV-negative controls were analysed. Primary outcome measures: Utilisation of hospice care services during the last year of life among PLWH and HIV-negative individuals. Results: A total of 20 413 subjects died during the 3 434 699 person-years of follow-up. Of the deceased patients, 2139 (10.5%) utilised hospice care services during their last year of life, including 328 (5.76%) PLWH and 1811 (12.30%) controls. Adjusting for demographics and comorbidities, PLWH were less likely to receive hospice care services during the last year of life, compared with HIV-negative individuals (adjusted OR: 0.66; 95% CI: 0.57 to 0.75). Conclusions: PLWH had significantly lower utilisation of hospice care services during the last year of life. Our results suggest that future hospice care programmes should particularly target PLWH to increase the optimal utilisation of hospice care services during EOL treatment.